Desenvolvimento de método para determinação do consumo de linha de costura industrial usada para a formação dos pontos 301 e 504 - Brandeli, Jacqueline Cristiane (2021)
The sewing industry has the sewing thread as one of the most used materials in its processes. Thus, there is need to calculate the consumption of this material, in order to plan and organize the company's production. The difficulty encountered by organizations in calculating this consumption refers to the need to develop new, more didactic and accessible methods. The following work sought to develop a method for calculating sewing thread consumption for Stitching 301 and 504, using the linear mass system, in order to compare it with an existing method. The results indicated the need for new tests for the developed method, focusing on the ambient humidity and the parameters of the machines used.